Winning with customers : a playbook for B2B - Pigues, D. Keith; Alderman, Jerry D. (Hoboken, N.J. : Wiley, 2010)
Do your customers make more money doing business with you? Knowing the answer can help you build measurable and valuable customer relationships, outperform the competition, and unlock profitable growth. Companies are blind to opportunities for profitable customer relationships without a deep understanding of how they create customer value relative to competitors. With a rigorous and measurable understanding of how customers make more money today and in the future with you, combined with supporting plans and tools to align the entire organization for success, a company can win and win big. "Winning with Customers" offers a step-by-step playbook to help companies develop this capability for themselves, act on it, build a culture around it and sustain it over time. The playbook includes case studies, interviews, and tools from leading B2B companies who have demonstrated success. Written by recognized business thought leaders and practitioners, this book will guide you to profitable growth. The book also serves as a launch point into a community of like-minded executives that includes a companion website which offers exercises, access to thought leaders, and other tools help you win with customers
Winning with Customers: A Playbook for B2B; Contents; Foreword by Karel Czanderna; Preface; Acknowledgments; Introduction by Glenn Dalhart; Chapter 1: Why We Lose; Chapter 2: Define Winning; Chapter 3: The Playbook; Chapter 4: Winning Metrics; Chapter 5: What Does Your Customer Think?; Chapter 6: Informing Decisions; Chapter 7: Executing Value Creation and Value Capture; Chapter 8: The Scoreboard; Chapter 9: Getting Started; Chapter 10: Sustaining and Scaling; Afterword; About the Authors; About the Contributors; Index; Appendix A: Our Approach to Certification and Building Capability.
Print version record.
John Wiley and Sons
Keywords: Customer relations -- Management; Consumer satisfaction; Customer services -- Management; Consommateurs -- Satisfaction; x; BUSINESS & ECONOMICS -- Marketing -- Industrial; Consumer satisfaction; Customer relations -- Management; Customer services -- Management